2016
DOI: 10.12659/msm.898569
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-1α and IL-6 is Associated with Progression and Prognosis of Human Cervical Cancer

Abstract: BackgroundIL-1α and IL-6 are associated with the prognosis of a wide range of cancers, but their value in cervical cancer remains controversial. The aim of this study was to investigate the expression of IL-1α and IL-6 in cervical cancer and their significance in clinical prognosis.Material/MethodsThe expression of IL-1α and IL-6 in 105 formalin-fixed, paraffin-embedded cervical cancer tissues and adjacent non-tumor tissues was examined by immunohistochemistry. The results were semi-quantitatively scored and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 28 publications
3
51
0
5
Order By: Relevance
“…Association between high plasma levels of IL‐1β and IL‐1B genotypes was observed in women with cervical cancer, and may be considered a candidate biomarker for the disease . The local expression of IL‐1α in the cancer tissue is positively correlated with cancer size, grade, and lymph node metastasis . Genotype of IL‐1 system proteins, plasma concentrations of IL‐β, and tissue expression of IL‐1α can be considered as valuable biomarkers for prognosis, and potential therapeutic targets.…”
Section: Il‐1 and Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Association between high plasma levels of IL‐1β and IL‐1B genotypes was observed in women with cervical cancer, and may be considered a candidate biomarker for the disease . The local expression of IL‐1α in the cancer tissue is positively correlated with cancer size, grade, and lymph node metastasis . Genotype of IL‐1 system proteins, plasma concentrations of IL‐β, and tissue expression of IL‐1α can be considered as valuable biomarkers for prognosis, and potential therapeutic targets.…”
Section: Il‐1 and Malignanciesmentioning
confidence: 99%
“…163,164 The local expression of IL-1α in the cancer tissue is positively correlated with cancer size, grade, and lymph node metastasis. 165 Genotype of IL-1 system proteins, plasma concentrations of ILβ, and tissue expression of IL-1α can be considered as valuable biomarkers for prognosis, and potential therapeutic targets.…”
Section: Il-1 and Malignanciesmentioning
confidence: 99%
“…Sapkota et al studied the relationship between IL‐1A gene locus and endometriosis and found that IL‐1A rs3783550 increased the risk of endometriosis in Europeans but was not statistically significant (Sapkota et al, ). Song et al found that IL‐1a was highly expressed in cervical cancer tissue and also found that the prognosis of patients with IL‐1a positive expression was worse than IL‐1a negative expression (Song et al, ). Another study has also shown that the level of IL‐1a was higher in peritoneal fluid and serum of endometriosis patients than in participants without the disease (Kondera‐Anasz, Sikora, Mielczarek‐Palacz, & Jońca, ).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on Cyr61-associated interactors, certain studies account for a signaling network in CC progression that clearly features the functional importance of Cyr61 activity. Song et al point out interleukins IL-1 and IL-6 as verisimilar valuable biomarkers and even potential therapeutic targets for CC (20). Most interestingly, Cyr61 is a known inducer of both factors, IL-1 (21) and IL-6 (22).…”
Section: Discussionmentioning
confidence: 99%